Case Study On Distribution Function Of SCM ( Supply-Chain Management) : Does The EFX's Distribution Center Concept Really Satisfy The Needs Of Customers? - Tee, Ng Kong (2001)
The objective of this project to study if the Distribution Center concept is the appropriate and feasible distribution approach for eFX to revitalize its distribution function of supply-chain management.